1974
DOI: 10.1002/eji.1830041103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitogenic stimulation of mouse lymphocytes by anti‐mouse immunoglobulin antibodies. I. Mode of action

Abstract: Inhibition of mitogenic stimulation of mouse I y m phocytes by ant i-mouse i m munogl obu I in antibodies 1. Mode of actionAntibodies with specificities for mouse p-chains and mouse K-and X-chains inhibit the stimulation of the major fraction of splenic lymphocytes from nude mice by lipopolysaccharide (LPS), by the purified protein derivative of tuberculin (PPD) and by fetal calf serum (FCS) t o differentiate into immunoglobulin (1g)-secreting, plaque-forming cells (PFC). Antibodies with specificities for mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
81
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 34 publications
11
81
1
Order By: Relevance
“…Alternatively, antibodies to cell-membrane antigens that are not part of receptor-combining sites may also prevent cell activation by external stimuli. In vitro studies with animal cells have demonstrated that mitogen-induced B-cell activation is blocked by antibody to immunoglobulin (29), antigen-induced T-cell proliferation is inhibited by antisera to histocompatibility region antigens (30), and the induction of in vitro colony-forming units in bone marrow cells treated with colony stimulating factor can be inhibited by antibody to brain (31 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, antibodies to cell-membrane antigens that are not part of receptor-combining sites may also prevent cell activation by external stimuli. In vitro studies with animal cells have demonstrated that mitogen-induced B-cell activation is blocked by antibody to immunoglobulin (29), antigen-induced T-cell proliferation is inhibited by antisera to histocompatibility region antigens (30), and the induction of in vitro colony-forming units in bone marrow cells treated with colony stimulating factor can be inhibited by antibody to brain (31 (32).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that activation of Notch signaling by Dll1 releases an inhibitory signal that otherwise maintains B cells in a nonsecreting blast state. An in vitro assay that reveals late inhibition of ASC differentiation is based on BCR cross-linking concomitant with LPS-mediated stimulation (15). In this assay, ASC inhibition is an ''all-or-nothing'' phenomenon at the single-cell level, dependent on BCR signal strength and BCR ligand concentration and independent of proliferation and Ig secretion rate (16).…”
Section: Dll1mentioning
confidence: 99%
“…RNA was extracted with TRIzol and reverse-transcribed by using SuperScript II RT and oligo(dT) [12][13][14][15][16][17][18] primer (Life Technologies, Gaithersburg, MD). Primer sequences are listed in SI Table 1.…”
mentioning
confidence: 99%
“…Stimulation with LPS also triggered a proliferation of ppc1-5H/ 1 B cells, but the response was slightly weaker than that of the ppc1-5H/ or non-tg B cells. This may be due to their prior BCR engagement (62).…”
Section: The Ppc1-5h/ 1 B Cells Respond Well To Anti-bcr and Mitogen mentioning
confidence: 99%